DIALEKTIKA HUKUM ISLAM DAN PERUBAHAN SOSIAL DI INDONESIA: TELAAH FATWA-FATWA TARJIH MUHAMMADIYAH - Imron Rosyadi (Tajdida: Jurnal Pemikiran dan Gerakan Muhammadiyah, 2014)
To avoid divisions Muhammadiyah members in practicing the teachings of Islam, Muhammadiyah established the Legal Affairs Committee (Tarjih). This assembly is tasked to examine issues related to fiqh and other religious issues. This paper examines about fatwas of Tarjih Muhammadiyah in responding to social change in Indonesia, concluded on dialectics Fatwa Tarjih with social change in Indonesia with all its dynamics in the following description. With reference to the dialectic model of Islamic law and social change, then the Fatwa Tarjih there are three models of dialectics (response), namely tahmil, taghyir, and Tahrim.